Gravesia serratifolia (Melastomataceae: Sonerileae), a new species from Marojejy National Park, Madagascar - Almeda, Frank; Ranarivelo, Heritiana (Phytotaxa, 2019)
Gravesia serratifolia, a new species from upper elevations of Marojejy National Park in northeastern Madagascar, is herein described, illustrated, mapped, and compared with similar species. It is readily characterized by its sparingly branched habit, leaf blades coarsely serrate with a moderate to sparse lepidote indumentum on both surfaces, inflorescence of few-flowered dichasia, calyx obsolete or evident as depressed truncate undulations with prominent calyx teeth that are laterally compressed when fresh, filaments with rusty-brown glandlike indumentum, and dorso-basal staminal appendages linear-oblong and widely spreading to coiled. A conservation assessment of Vulnerable is recommended for this species based on IUCN Red List Categories and Criteria.